O papel dos chefs-celebridades na construção do espetáculo da alimentação: análise discursiva das revistas de gastronomia de luxo - Luderer, Cynthia Arantes Ferreira (2013)
The objective of this research is to investigate the construction process of the image of chefs as celebrities in the boom period of gastronomy in Brazil, examining the logic of the spectacle inherent in new food models implemented in the last 20 years. The cuisine has gained importance in Brazil since 1990, becoming valued and exposed in different medium. In this context the created scenario results is an outstanding image creation of the chefs, and other professionals, as restauranters , nutritional specialists, students and technologists speeches, including press officers, journalists and critics. The new proposals and food choices are now disclosed by these actors within a show, where the audience is asked to participate in blogs, television, radio, newspapers, reality shows and magazines in the area. This confluence arises our research question: how the communicative devices from luxury magazines intervene in the construction of a show in which chefs are transformed into celebrities and as such promote new food fashion to be followed? The research corpus is composed of 25 copies of the magazines: Gula, Alta Gastronomia, Menu, Prazeres da Mesa e Go Where-Gastronomia, published in an interval of five years, since 1991, as well as the annual guide gastronomic magazine SEE Eating and Drinking in the period 2004-2010. The analysis methodology used in this research was the analysis of discourse anchored in Charaudeau and Prado, from which we study the contracts of communicative media printed evaluated. In addition to the bibliographic resources, the study was conducted in the field, with participant observation, interviews with Brazilian professionals and foreigners working in the gastronomic field and questionnaires administered to students. The central hypothesis indicates that the chefs presented as celebrities become the central characters of narratives of speakers of an emerging market power, which excels in dictating rules and models to keep a new cycle of active consumption. The concept of the field of gastronomy is supported by Bourdieu and culinary capital is presented by Naccarato and Ms. LeBesco. Aspects of the spectacle, which embodies the cuisine, were approached from Debord. Besides authors who discuss semiotics and socio cultural urban consumption, to address aspects relevant to food anthropology, this study is based on Arnaiz and Contreras